Stratospheric Quasi Biennial Oscillation Modulations of Migrating Diurnal Tide in the Mesosphere and Lower Thermosphere Over the Low and Equatorial Latitudes. Issue 7 (6th July 2021) - Pramitha, M.; Kumar, K. Kishore; Ratnam, M. Venkat; Praveen, M.; Bhaskara Rao, S. Vijaya
Abstract: Horizontal wind measurements using meteor radars located at Thumba (8.5°N, 77°E; 2006–2015) Kototabang (0.2°S, 100.3°E; 2002–2017) and Tirupati (13.63°N, 79.4°E; 2013–2017) in the mesosphere‐lower thermosphere (MLT) and Specified Dynamics Whole Atmosphere Community Climate Model (SD‐WACCM) simulations are employed for investigating the diurnal tide variability at quasi‐biennial scales. The model simulations are evaluated using the meteor radar observations at three tropical locations. WACCM simulations could reproduce the seasonal evolution of diurnal tides very well over Thumba and Tirupati but there are small discrepancies over Kototabang. In order to investigate the modulation of the diurnal tide amplitudes in the MLT region by the stratospheric quasi‐biennial oscillation (SQBO), deseasonalized perturbations of diurnal tides and stratospheric winds are analyzed. A very good correspondence is found between meridional diurnal tide perturbation amplitudes and the SQBO with positive tidal perturbations during the eastward phase of SQBO and negative perturbations during the westward phase over Thumba and Tirupati. SQBO modulations of diurnal tides at global scales exhibits a positive correlation between the meridional diurnal tide perturbation with SQBO winds at 20 hPa and a negative correlation with SQBO winds at 70 hPa within ±40° latitude, except over the equator. It is also noted that the equatorial electrojet strength, is modulated by the SQBO over the Thumba, which is a dip equatorial location. The significance of present study lies in evaluating WACCM simulations at tropical locations using meteor radar measurements and in investigating the SQBO modulations of diurnal tides at global scales. Plain Language Summary: Atmospheric tides are global scale oscillations having periods that are harmonics of solar day (24‐, 12‐, 8‐h, etc.) and play a significant role in coupling lower and middle/upper atmosphere. Tides are generated in the troposphere/stratosphere and propagate upwards. In order to conserve the momentum, the amplitude of tides increases with altitude in response to decreasing density with altitude. Among many atmospheric waves present in the mesosphere‐lower thermosphere (MLT), diurnal tides (24‐h period) have the largest amplitudes over the low‐latitudes and thus play a key role in shaping the structure and dynamics of this region. Even though tides are well represented in numerical models, time‐to‐time evaluation of these models against observations from several ground‐based measurements is needed to employ them in day‐to‐day research applications. In the present study, SD‐WACCM model simulations of mean winds and diurnal tides in the MLT region are evaluated using meteor radar observations over three tropical locations [Thumba (8.5°N, 77°) Kototabang (0.2°S, 100.3°E) and Tirupati (13.63°N, 79.4°E)]. There exists a long‐period oscillation in the stratosphere known as stratospheric quasi‐biennial oscillation (SQBO), which is believed to modulate the amplitude of diurnal tides at interannual scales. The present study also investigates the relationship between SQBO and the tidal variability in the MLT region. The results show significant correlation between the SQBO phase and the deseasonalized diurnal tide amplitudes in the MLT region. Diurnal tide amplitudes are relatively larger during the eastward phase as compared to the westward phase of the SQBO. It is also noted that the strength of the equatorial electrojet is also modulated by the SQBO. The WACCM simulations could reproduce this feature very well. The model simulations are further employed to study the response of diurnal tide amplitude to the phase of the SQBO at global scales. The results show that the SQBO phase influences the diurnal tide amplitude in the latitude belt of 40°N–40°S except at the equator. Thus, the present study evaluates WACCM simulations using meteor radar observations and discusses the role of SQBO in modulating the diurnal tide amplitudes over three tropical latitudes. Key Points: Response of diurnal tide in the mesosphere‐lower thermosphere (MLT) to the stratospheric quasi‐biennial oscillation (SQBO) is investigated over three locations using meteor radar observation and Whole Atmosphere Community Climate Model (WACCM) simulations The monthly mean tidal variability in the MLT region is highly correlated with stratospheric winds at 20–40 hPa pressure level Stratospheric QBO modulation of tidal variability in the MLT imposes the QBO signature in the equatorial electrojet